GAMBARAN HISTOLOGI DAGING AYAM KAMPUNG (Gallus domesticus) YANG DIBERIKAN EKSTRAK DAUN BELIMBING WULUH (Averrhoa bilimbi) - Moenek, Devi Y. J. A.; Toelle, Novianti Nellyani (JURNAL KAJIAN VETERINER, 2021)
Star fruit leaf (Averrhoa bilimbi) in this study were extracted making use of the maceration method and the solvent was absolute ethanol. This study aims to see the effect on free-range chicken meat due to the administration of wuluh starfruit leaf extract. Histological description of the meat was taken from the chest muscle (M. pectoralis) and thigh muscle (M. femoralis) which had previously been treated with starfruit leaf extract. The analysis was carried out descriptively by looking at the histology of free-range chicken meat and compared with the normal picture. The results indicated there is no effect between the administration of starfruit leaf extract on the histology of native chicken meat. It can be seen that the muscle structure is normal, there are no dimensions and shape-changing of the muscle fibers and connective tissue. Conclusions can be drawn that the antibacterial ability of starfruit leaf, shows no effect on the chest and thigh muscles structure of native chickens.